EDUKASI FRUGRAL LIVING: FROM SMART SPENDING TO HAPPY LIVING BAGI IBU – IBU PERSIT - Adnanti, Wenny Ana; Widiastuti, Tantri (Fokus ABDIMAS, 2025)
This community service activity aims to improve the financial literacy of Persit mothers through frugal living education, a frugal lifestyle that emphasizes wise financial management without sacrificing quality of life. This program teaches the principles of smart spending, effective budgeting, and a positive financial mindset using the approach of behavioral economics and Maslow’s hierarchy of needs theory. Through counseling and interactive workshops, participants are equipped with skills to distinguish between needs and wants, manage expenses efficiently, and apply financial planning methods such as the 50/30/20 rule. Evaluations show that 90% of participants experienced an increase in their understanding of household financial management and have begun implementing budgeting strategies and financial record-keeping. Discussion sessions revealed that participants feel more confident in making more rational and sustainable financial decisions. The results of this activity indicate that frugal living education has a positive impact on shaping a smarter and more disciplined financial mindset. Therefore, this program is recommended for further development with additional materials on investment and financial risk management to enhance overall family well-being.Keywords: frugral living, smart spending, behavioral economics